Pemanfaatan SIG dalam Analisis Perubahan Garis Pantai Menggunakan Metode DSAS di Pantai Lampuuk, Kab. Aceh Besar Tahun 2005-2025 - Prayogo, Bintang Aditya; Zalmita, Novia; Yulianti, Fitriani; Furqan, Muhammad Hafizul (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Indonesia is a maritime country consisting of 17,000 islands with a sea area of ​​around 70%. As a maritime country with a coastline of 108,000 km and making Indonesia the country with the longest coastline. The coastline is the boundary line between land and sea water which has a non-permanent or dynamic nature. Changes in this coastline are usually dominated by erosion and sedimentation phenomena that occur along the coastline, in addition to these two phenomena, natural disasters such as tsunamis can also have an impact on a coastline. As in late 2004, Aceh experienced a fairly severe tsunami with a strength reaching 9.1 magnitudes which caused almost the entire southwestern part of Aceh to be damaged and Lampuuk beach is one of the beaches that has clearly experienced changes due to the impact of the tsunami. A coastline can be measured for changes by comparing one period of a coastline with another period. A geographic information system is a computer-based mapping system used to enter, store, recall, manage, analyze, and produce geographically referenced data or geospatial data. By using GIS we can analyze coastline changes by comparing multitemporal image data. This study aims to determine the changes in the coastline that occurred on Lampuuk Beach, Lhoknga District, Aceh Besar Regency. This study uses Google Earth image data from 2005-2025 to determine the changes in the coastline that occurred and to determine the extent of abrasion and accretion that occurred on Lampuuk Beach using the digital shoreline analysis system (DSAS) method. The results of this study indicate that within a period of 20 years along the Lampuuk coastline, erosion and sedimentation phenomena in the form of abrasion and accretion have occurred, where the highest abrasion value along Lampuuk Beach reached 1.09 hectares and the highest accretion value along Lampuuk Beach reached 2.88 hectares.